2016
DOI: 10.1039/c6ra10549a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spermine on the structure, thermal stability and activity of bovine pancreatic trypsin

Abstract: This work studied the interaction between spermine and trypsin at pH 8.0. The thermal stability of trypsin was investigated in the presence of spermine over a temperature range (from 293 K to 353 K).Additionally, the conformational change of trypsin induced by spermine was analyzed by UV-Vis absorption and fluorescence spectra. The effect of spermine on trypsin activity was studied at 37 °C and pH 8.0, using Tris-HCl as a buffer. The fluorescence spectroscopy results indicated that the binding of spermine to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recent studies, reported that many viruses have been shown to entail that polyamines are required for their replication cycle, including DNA and RNA polymerization, nucleic acid packaging, and protein synthesis [16]. Another important function of polyamine, especially spermine has been recently discovered that it could be considered as an activator and stabilizer for bovine trypsin [17].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Recent studies, reported that many viruses have been shown to entail that polyamines are required for their replication cycle, including DNA and RNA polymerization, nucleic acid packaging, and protein synthesis [16]. Another important function of polyamine, especially spermine has been recently discovered that it could be considered as an activator and stabilizer for bovine trypsin [17].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Recent studies, reported that many viruses have been shown to entail that polyamines are required for their replication cycle, including DNA and RNA polymerization, nucleic acid packaging, and protein synthesis [16]. Another important function of polyamine, especially spermine has been recently discovered that it could be considered as an activator and stabilizer for bovine trypsin [17].…”
Section: Mini Reviewmentioning
confidence: 99%